Anticoagulant, anti-inflammatory, antiviral and antitumor properties of heparins - V. O. Bitsadze; E. V. Slukhanchuk; J. Kh. Khizroeva; M. V. Tretyakova; N. V. Pyatigorskaya; S. V. Akinshina; N. A. Makatsariya; K. E. Gotsiridze; N. N. Babaeva; K. N. Grigoreva; A. S. Shkoda; I. Elalamy; et al. (Акушерство, гинекология и репродукция, 2021)
Our knowledge regarding chemical structure and properties of heparin and its derivatives, including biological properties in blood plasma, on the cell surface and while interacting with receptors, has been progressively growing. New insights are followed by the expansion of therapeutic opportunities and indications for the use of heparins. There are prerequisites for the creation of new generation drugs with modified properties that reduce a bleeding risk while applied for a non-anticoagulant goal. The non-anticoagulant heparin properties allow to consider it as a candidate for pathogenetic treatment of patients with COVID-19. This review focuses on the anticoagulant and non-anticoagulant heparin properties as well as the underlying molecular mechanisms.